Implementasi Perencanaan Strategis Berbasis Matriks SWOT pada Agen Perjalanan Umrah Perspektif Etika Bisnis Islam: Studi Kasus Travel Makkata Umroh - Ismi Fauzia Ismail; Salsabila (Ekodestinasi, 2025)
The rapid growth of Indonesian Umrah pilgrims is currently facing systemic challenges, including disruptions from the Nusuk digital platform policy (Saudi Vision 2030) and the onslaught of independent Umrah trends. This study aims to evaluate the company's competitive position and formulate operational tactics for the Travel Makkata Umroh Pontianak branch using the SWOT matrix instrument harmonized with the perspective of Islamic business ethics. This research uses a descriptive qualitative method. Data collection was conducted through in-depth interviews with top management and documentation studies between December 4 and 9, 2024. The analysis results show that the company's strategic position is in Quadrant I, which recommends aggressive growth steps. Corporate governance is based on the implementation of Islamic business ethics through FAST (Fathonah, Amanah, Shiddiq, Tabligh) capabilities which serve as the main guiding pillars. The formulated strategy blueprint includes geographic and demographic expansion, commercial financing alliances, guerrilla marketing tactics, and internal business process reengineering to mitigate public trauma against problematic agencies.